The Expression of Egfl7 in Human Normal Tissues and Epithelial Tumors. Issue 1 (January 2013) - Fan, Chun; Yang, Lian-Yue; Wu, Fan; Tao, Yi-Ming; Liu, Lin-Sen; Zhang, Jin-Fan; He, Ya-Ning; Tang, Li-Li; Chen, Guo-Dong; Guo, Lei
Background and aims: To investigate the expression of Egfl7 in normal adult human tissues and human epithelial tumors. Methods: RT-PCR and Western blot were employed to detect Egfl7 expression in normal adult human tissues and 10 human epithelial tumors including hepatocellular carcinoma (HCC), lung cancer, breast cancer, prostate cancer, colorectal cancer, gastric cancer, esophageal cancer, malignant glioma, ovarian cancer and renal cancer. Immunohistochemistry and cytoimmunofluorescence were subsequently used to determine the localization of Egfl7 in human epithelial tumor tissues and cell lines. ELISA was also carried out to examine the serum Egfl7 levels in cancer patients. In addition, correlations between Egfl7 expression and clinicopathological features as well as prognosis of HCC and breast cancer were also analyzed on the basis of immunohistochemistry results. Results: Egfl7 was differentially expressed in 19 adult human normal tissues and was overexpressed in all 10 human epithelial tumor tissues. The serum Egfl7 level was also significantly elevated in cancer patients. The increased Egfl7 expression in HCC correlated with vein invasion, absence of capsule formation, multiple tumor nodes and poor prognosis. Similarly, upregulation of Egfl7 in breast cancer correlated strongly with TNM stage, lymphatic metastasis, estrogen receptor positivity, Her2 positivity and poor prognosis. Conclusions: Egfl7 is significantly upregulated in human epithelial tumor tissues, suggesting Egfl7 to be a potential biomarker for human epithelial tumors, especially HCC and breast cancer.